Od rewolucji proletariackiej do powstania narodowego. Przegląd konceptualizacji „Solidarności” w naukach społecznych i humanistycznych - Brzechczyn, Krzysztof (Pamięć i Sprawiedliwość, 2013)
The purpose of this paper is to review of various approaches to „Solidarność” in subject-matter literature. The author is going to seek answer to the following interpretative question: whether a given conceptualization grasp „Solidarność” movement in dynamic or in static way. In the second part of the paper interpretations of „Solidarność” in analytical categories of insurrection, civil, postmodern, religious, republican, revolutionary and social movements are presented. Finally, the author tries to identify reasons of dynamic or static approach to „Solidarność”.